Hyperphosphatemia and Cardiovascular Disease - Zhou, Chao; Shi, Zhengyu; Ouyang, Nan; Ruan, Xiongzhong (Frontiers in Cell and Developmental Biology, 2021)
Hyperphosphatemia or even serum phosphate levels within the “normal laboratory range” are highly associated with increased cardiovascular disease risk and mortality in the general population and patients suffering from chronic kidney disease (CKD). As the kidney function declines, serum phosphate levels rise and subsequently induce the development of hypertension, vascular calcification, cardiac valvular calcification, atherosclerosis, left ventricular hypertrophy and myocardial fibrosis by distinct mechanisms. Therefore, phosphate is considered as a promising therapeutic target to improve the cardiovascular outcome in CKD patients. The current therapeutic strategies are based on dietary and pharmacological reduction of serum phosphate levels to prevent hyperphosphatemia in CKD patients. Large randomized clinical trials with hard endpoints are urgently needed to establish a causal relationship between phosphate excess and cardiovascular disease (CVD) and to determine if lowering serum phosphate constitutes an effective intervention for the prevention and treatment of CVD.